Welcome to Journal of Ethnobiology and Ethnomedicine - Price Lisa; Pieroni Andrea; Vandebroek Ina (BMC, 2005)
Abstract Ethnobiology is a multidisciplinary field of study that draws on approaches and methods from both the social and biological sciences. Ethnobiology aims at investigating culturally based biological and environmental knowledge, cultural perception and cognition of the natural world, and associated behaviours and practices. Ethnomedicine is concerned with the cultural interpretations of health, disease and illness and also addresses the health care seeking process and healing practices. Research interest and activities in the areas of ethnobiology and ethnomedicine have increased tremendously in the last decade. Since the inception of the disciplines, scientific research in ethnobiology and ethnomedicine has made important contributions to understanding traditional subsistence and medical knowledge and practice. The Journal of Ethnobiology and Ethnomedicine (JEE) invites manuscripts and reviews based on original interdisciplinary research from around the world on the inextricable relationships between human cultures and nature, on Traditional Environmental Knowledge (TEK), folk and traditional medical knowledge, as well as on the relevance of the above for Primary Health Care (PHC) policies in developing countries.